Study Scientific Methods for Small Project Selection in an Iraqi Environment (Journal of University of Babylon for Engineering Sciences, 2018)
The Research aims to study the scientific methods of selecting the best project in a specific environment. The selection of the best small project is an important step for any executive authority or contractor and it is essential for achieving a specific goal (whether it is a profit or provision of certain goods or any other objective). In order to have a true choice, the project evaluation will be the basis of choice. ؛ Project evaluation defined as the an organized assemblage of data about the activities characteristic and results of actions or activities, for determining its value. It can afford a plurality of significant information project's outcomes; it is a systematic method of reflecting on and calculating the wealth of what is being done (i.e. project, events, and program). Evaluation is usually understood as a product or an activity taking place at the end of a project. However, evaluation should be considered as a process, occurring across all phases of a project, used for determining what does occurred and if the early project objectives have been achieved. The aim of this paper is to study the scientific approaches and steps to make a decision to select the best small projects in a specific environment for implementing within the constraints of the investor and the governorate strategic plan.